Knowledge and use of insecticide treated nets as a malaria preventive tool among pregnant women in a local government area of Lagos state, Nigeria - B. A. Aina, F. A. Ayeni (Journal of Applied Pharmaceutical Science)
Malaria has been described as the foremost public health concern in tropical and subtropical regions of the world, Nigeria inclusive. This survey set out to assess the knowledge, attitude and practice on the use of ITNs as a malaria preventive tool among pregnant women and to determine its level of recommendation and proper instructions given by pharmacists. Structured questionnaires were administered to pregnant women attending antenatal clinics at two selected hospitals in Alimosho Local Government Area (ALGA) of Lagos State and also to community pharmacists practicing in the same ALGA. Data was analyzed using Epi Info 2002 and Microsoft Excel. Forty eight community pharmacists and 163 pregnant women participated in the study. About 77 and 91% of pregnant women were aware of ITNs at Igando GH and the private hospital respectively. Only 11.2% and 37.5% actually used it. Majority of the pharmacists (95.8%) recommended the use of ITNs and 95% of them also gave counsel on ITN use while 5% did not. There is a wide difference between the level of awareness and the rate of use of ITNs by pregnant women. More emphasis should be placed on ownership and use of ITNs so that the benefit of its protection can be derived.
Keywords: ITNs, Alimosho Local Government Area (ALGA), Igando General Hospital (IGH), Private Hospital (PH), Pregnant women.